Influence of available nitrogen and rice genotype on associative dinitrogen fixation - Malarvizhi, P.; Ladha, J.K. (Wiley, 1999)
Rice (Oryza sativa L.) genotypes with a high ability to support biological N2 fixation are of interest because they would enhance N gains in the rice‐soil system without changing existing cultural practices. Pot experiments were conducted in a greenhouse during the 1994 wet season to determine the amount of N2 derived from the atmosphere (Ndfa) by 10 rice genotypes grown in three soils with varying levels of initial soil‐NH+4‐N. Enriched 15N and natural abundance δ15N dilution methods were employed. Flooded soils were puddled with and without 99.5 atom 15N%‐labeled urea to minimize spatial variation of the isotope. The integrated 15N enrichment of plant available N, calculated using a model that accounts for temporal changes in the isotopic composition, was used as a reference to estimate genotypic differences in Ndfa. The 15N enrichment of soil available N declined exponentially and was half the original level at 122 d. The δ15N values correlated with atom 15N% excess of enriched 15N for the rice genotypes grown in two out of three soils. Percentage Ndfa for the genotypes across three soils ranged from 4.2 to 32.2 when calculated using as a reference plant, and from 10.8 to 35.9 when calculated using 15N enrichment of soil available N as a reference. Genotypic differences were significant and more pronounced at low soil‐NH+4‐N (11 mg kg‐1) than at higher soil‐NH+4‐N (79 and 92 mg kg‐1); they ranged from 14.9 to 35.9% at low N and from 10.8 to 23.6% at high N. Some genotypes consistently gave either high or low Ndfa. Because of the low levels and narrow range of genetic differences in associative N2 fixation, the potential for its improvement through breeding appears to be limited.